Psilorhynchus khopai, a new fish species (Teleostei: Psilorhynchidae) from Mizoram, northeastern India - Lalramliana, Lalramliana; Solo, Beihrosa; Lalronunga, Samuel; Lalnuntluanga, Lalnuntluanga (Zootaxa, 2014)
Psilorhynchus khopai, a new species of Psilorhynchidae, is described from Tuisi River, a tributary of Kaladan River, in Mizoram, India. The species is proposed to be a member of the Psilorhynchus homaloptera species group and can be distinguished from its congeners in having a forked caudal-fin with 9 + 9 principal caudal rays, 14–17 predorsal scale rows, 39–41 lateral-line scale rows, mid-lateral body with 9–12 indistinct small dark brown round markings forming a lateral stripe and, in life, a faint gold stripe along dorsal midline with 4–5 black spots between dorsal fin and caudal fin base.